Funerary Monuments of 1821 Revolutionaries in Athens First Cemetery - Pavlopoulos, Dimitris; Antonopoulou, Georgia; Giochalas, Michael (The Historical Review/La Revue Historique, 2022)
Previously inaccessible archival sources, as well as in situ observation, provide useful information on the corpus of funerary monuments of 1821 Revolution figures in Athens First Cemetery. These spatially dispersed monuments are mostly unknown. Being both works of art and bearers of historical contexts and narratives, they reflect the beliefs and trends of nineteenth-century Greek society. The fighters have become interlocutors with the ancient predecessors, thus dictating to the collective consciousness and subconsciousness the historical necessity of continuity and of the mission entailed in it. Within the context of the fluctuating geography and anthropogeography of Athens First Cemetery, and under the pressure of its permanent usage, issues of collective memory and preservation have emerged. Consequently, the practices of the local authorities in this regard constitute an interesting field of research.